Light brown apple moth, Epiphyas postvittana (Walker) (Insecta: Lepidoptera: Tortricidae) - Caitlin A. Lewis; Amanda C. Hodges (EDIS)
EENY-469, a 7-page illustrated fact sheet by Caitlin A. Lewis and Amanda C. Hodges, is part of the Featured Creatures collection. It describes this extremely polyphagous insect, native to Australia, that is considered to be a major pest of fruits and ornamental plants — distribution, description and life cycle, damage, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, January 2010.